2021
DOI: 10.1017/s0954422421000317
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and prebiotics: potential prevention and therapeutic target for nutritional management of COVID-19?

Abstract: Scientists are working to identify prevention/treatment methods and clinical outcomes of Coronavirus Disease 2019 (COVID-19). Nutritional status and diet have a major impact on the COVID-19 health-disease process, mainly due to the bidirectional interaction between gut-lung axis. Individuals with inadequate nutritional status have a pre-existing imbalance in the gut microbiota and immunity as seen in obesity, diabetes, hypertension, or other chronic diseases. Communication between the gut microbiota and lungs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 181 publications
0
17
0
1
Order By: Relevance
“…In fact, probiotics have been shown to have a larger beneficial effect in inflammatory biomarker levels such as IL-6 and CRP as a measure of low-grade inflammation than even Angiotensin Receptors Blockers, omega-3, metformin, resveratrol, and vitamin D ( 235 ). These gut-microbiome modulating nutraceuticals have shown to serve also as immunomodulators leading to downregulation of the low-grade inflammation state ( 236 , 237 ), leading to an overall reduction or attenuation of COVID-19 related symptoms such as “diarrhea, abdominal pain, vomiting, headache, cough, sore throat, fever, and viral infection complications such as acute respiratory distress syndrome (ARDS)” ( 238 ). By close monitoring of potential interactions with diabetes and antiviral drugs, especially conserving that many antibiotics given during COVID-19 infection may further lead to gut microbiome dysbiosis ( 233 ), probiotics, along with pre- and synbiotics, may serve as therapeutic agents with low adverse event incidence for treatment of diabetics with COVID-19 ( 239 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, probiotics have been shown to have a larger beneficial effect in inflammatory biomarker levels such as IL-6 and CRP as a measure of low-grade inflammation than even Angiotensin Receptors Blockers, omega-3, metformin, resveratrol, and vitamin D ( 235 ). These gut-microbiome modulating nutraceuticals have shown to serve also as immunomodulators leading to downregulation of the low-grade inflammation state ( 236 , 237 ), leading to an overall reduction or attenuation of COVID-19 related symptoms such as “diarrhea, abdominal pain, vomiting, headache, cough, sore throat, fever, and viral infection complications such as acute respiratory distress syndrome (ARDS)” ( 238 ). By close monitoring of potential interactions with diabetes and antiviral drugs, especially conserving that many antibiotics given during COVID-19 infection may further lead to gut microbiome dysbiosis ( 233 ), probiotics, along with pre- and synbiotics, may serve as therapeutic agents with low adverse event incidence for treatment of diabetics with COVID-19 ( 239 ).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics and prebiotics are the two components in our diet that can affect the microbiome. Nutritional status and diet play a crucial role in COVID-19, predominantly owing to the bidirectional interaction between the lungs and the gut microbiota [ 146 ]. Figure 5 depicts the interactions between the human gut and lungs and the potential positive immune responses triggered by probiotics and prebiotics.…”
Section: Potential Preventive And/or Therapeutic Effects Of Prebiotic...mentioning
confidence: 99%
“…As acute lung injury-mediated lung dysbiosis has been demonstrated to be associated with blood-mediated modulation of the gut microbiota, coronavirus disease 2019 (COVID-19) may induce lung microbiota disruption, thus driving the imbalance of the gut microbiota ( Olaimat et al., 2020 ). By investigating the lung tissue of deceased COVID-19 patients, it was found that lung microbiome dysbiosis in severe COVID-19 patients was characterized by enrichment of bacteria that are primarily responsible for the highest rates of multidrug resistance and mortality; therefore, continuous monitoring of the lower respiratory tract microbiota is needed for prompt and personalized treatment ( Batista et al., 2021 ). The occupational health impact of respiratory infectious diseases is costly to the economy and the healthcare system.…”
Section: Can Probiotics Flatten the Curve Of The Covid-19 Pandemic?mentioning
confidence: 99%